Participative politic processes for an inclusive and consensual use of land. the mendoza, argentina, case (2009)
The present article intends to meditate on one of the so many challenges for the rights and for the benefits of the citizenship: the use of the land, inclusive and agreed, in Mendoza’s County, Argentina. In populations, as the case of Mendoza, where the physical singularity and aridity of the floor condition the human establishment and the economic activities, the territory becomes a fundamental basic resource to protect, and its use and fair and equal distribution are vital for the local society. However, in the current social, political and economic context, the absence of normative, the public inaction and the scarce civic participation have favored a disordered urban growth and an inadequate use of the floor and of the infrastructure. Situations of social fragmentation, inequality and concentration of the socioeconomic and political processes are deepened. In the year 2006, the Legislature of the County begins the treatment of bills of floor use. Initially, the legislative debate generated favorable expectations in the citizenship, however, scientific, professionals and technicians noticed that the proposals had numerous technical and legal difficulties. The same ones committed the rational and inclusive use of the floor seriously. This way, a process of civic discussion the one begins which is analyzed in this article.